Partial discharge measurement and vibration monitoring on power transformer case study on power transformer with high level noise (75.22 dB) - Solin, I. K. (AIP Publishing, 2014)
Proceedings of the 9th International Conference on the Properties and Applications of Dielectric Materials (ICPADM) 2009 at Harbin, China on 19 July 2009 through 23 July 2009. Link to publisher's homepage at http://ezproxy.unimap.edu.my:2080/Xplore/dynhome.jsp?tag=1